Transportation of magnetized micropolar hybrid nanomaterial fluid flow over a Riga curface surface. (March 2020) - Abbas, Nadeem; Malik, M.Y.; Nadeem, S.
Highlights: Here hybrid nanofluid of micropolar fluid is addressed. Energy equation is modeled subject to thermal slip effect. Numerical solutions are calculated via shooting method. Flow over a curved surface is discussed. Abstract: We deliberated the flow of magnetized micropolar hybrid nanoparticles fluid flow over the Riga curved surface. Exponentially stretching and slip effects are also considered in this analysis. Mathematical model has been established on the base of assumptions in the form of partial differential equations. Such equations are renewed into ordinary differential equations utilizing similarity transformations. Reduced model has been elucidated by means of bvp4c scheme. Impacts of physical parameters namely as stretching parameter R0, curvature parameter K, solid nanoparticle volume fraction Φ2, micropolar parameter K1, microgyration parameter n, thermal slip parameter M, partial slip parameter γ, modified Harman number ∅ and dimensionless parameter ω. Magnetic parameter β and reciprocal magnetic Prandtl number λ are depicted by means of numerically and graphically. Our results help in the field of engineering and industrial. This model is presented in the first time through literatures. Our interest of study is to be analyzed about the heat transfer rate of magnetized micropolar hybrid nanomaterial fluid over a Riga curved surface. Comparison with the literature has been worked out and excellent agreement is found.